Speech rate perception in audios in Easy Language amongst individuals with intellectual disabilities - Marina Pujadas-Farreras (Cadernos de Tradução, 2025)
Easy Language is a simplified language variety designed to enhance accessibility for individuals with comprehension difficulties. While its application in audiovisual contexts—such as podcasts and radio news produced in various languages—has garnered interest, guidelines for its oral and audio use remain limited. One common recommendation is to adopt a slower speech rate, yet specific guidance is rarely provided. Furthermore, it must be considered that speech rate perception is influenced by various factors, including language-specific norms and cognitive load, complicating the development of universal recommendations. This intralingual study investigates speech rate perception among 35 native Catalan-speaking individuals with intellectual disabilities, evaluating responses to Easy Language recordings in Catalan at four speech rates: 130 wpm, 150 wpm, 170 wpm, and 190 wpm. Participants rated the perceived speed of each recording on a five-point Likert scale, ranging from “too slow” to “too fast”. Results revealed two distinct patterns: one subgroup found all speech rates acceptable, while the other exhibited greater variability in ratings, reflecting a more refined perception or reduced acceptability of certain speeds. A significant age difference was observed between these subgroups, though no differences were identified in cognitive performance, as measured by Raven scores.